Karakteristik bakso tempe dengan penambahan tepung kulit bawang merah (Allium cepa L.) sebagai pangan fungsional - Setiawan, Sia, Clarissa Eleora; Dewi, Lusiawati (ARGIPA (Arsip Gizi dan Pangan), 2025)
As public awareness of the importance of health continues to grow, the demand for functional food products is also increasing. Red onion skins, often discarded as waste, are rich in antioxidants, while tempeh serves as a high-quality source of plant-based protein. These two local ingredients hold great potential for the development of diversified meatball products, appealing to a wide range of consumers, including vegetarians. This study aimed to evaluate the characteristics of tempeh-based meatballs enriched with red onion skin flour, focusing on consumer-preferred formulations, nutritional value, and functional food potential. A Completely Randomized Design (CRD) was employed with four treatment groups (0 g, 1.5 g, 3 g, and 4.5 g of red onion skin flour) and three replications. The addition of red onion skin flour significantly affected the color of the tempeh meatballs (p < 0.05). The optimal formulation was identified as F3, which contained 3 grams of red onion skin flour. This formulation received the highest average sensory scores: color (3.88), aroma (3.28), taste (3.44), and texture (3.24). Furthermore, the best formulation met the Indonesian National Standard (SNI 01-3820-2014) and demonstrated promising nutritional and functional properties, including antioxidant activity of 41.06%, protein content of 16.92%, moisture content of 35.82%, and ash content of 1.14%.